SOLUSI PENYELESAIAN KONFLIK DALAM MENANGANI KONFLIK SOSIAL DI WILAYAH KABUPATEN BIMA - Ahmad Yasin; Damhuji; Dati Amaliyah (Bajang Institute, 2021)
In overcoming the rampant conflicts that occurred in Bima Regency, of course, it is not enough to rely solely on legal instruments, but it is also necessary to examine the root of the problem thoroughly, including aspects of education, economy, politics, social and culture. With reference to the background of the problem above, the problem in this study is how to find the right solution to deal with social conflicts in Bima Regency with the aim of knowing the efforts or steps taken in resolving social conflicts in Bima Regency. This research is an empirical legal research, the approach used is a sociological perspective. The data source is field data, the method used is structured interview and observation, and the data analysis technique used is the deductive method. The solution to resolving conflicts or brawls between villages can be done in the following ways, such as building a synergistic and strong cooperative relationship between all parties, from the government, security forces, universities, media, private sector, and the community supported by sufficient budget to carry out these activities. mediation, dialogue, empowerment/training, and education for the younger generation, conducting raids and sweeping homemade weapons, arrows and sharp weapons, eradicating provocations and thuggery, stopping drug trafficking, gambling, and night entertainment, enforcing the law quickly and fairly, minimize the practice of KKN in government and society, and build a professional and fair system in distributing economic resources, such as building a professional Bazda.